Family care to individuals dependent on alcohol and other drugs - Soccol, Keity Laís Siepmann; Terra, Marlene Gomes; Girardon-Perlini, Nara Marilene Oliveira; Ribeiro, Danilo Bertasso; Silva, Cristiane Trivisiol da; Camillo, Lucia Amabile (Rev Rene, 2013)
This is a qualitative, exploratory and descriptive research, which aimed to describe the family care given to the individual dependent on alcohol and other drugs. For data collection we used the interview, open, free and recorded, which was performed in August and September 2011. The 11 subjects were relatives of the individuals dependent on alcohol and other drugs, involved in family groups conducted at the Psychosocial care Center for Alcohol and Drugs. From the content analysis of these interviews, two categories were revealed: care actions in the perception of family caregivers, and care to minimize conflicts in family relations. The way the family takes care of the relative dependent on alcohol and other drugs has the purpose of meeting the physical and emotional demands, as well the interpersonal relationships, as it is concerned with the wellbeing of the chemically dependent relative.DOI: https://doi.org/10.15253/2175-6783.20130003000011